Menu Close

f-R-R-g-R-R-f-xg-f-x-g-y-g-xy-f-x-g-y-d-fg-dx-




Question Number 821 by 123456 last updated on 17/Mar/15
f:R→R  g:R→R  f(xg)=f(x)g(y)  g(xy)=f(x)+g(y)  ((d(fg))/dx)=?
f:RRg:RRf(xg)=f(x)g(y)g(xy)=f(x)+g(y)d(fg)dx=?
Answered by prakash jain last updated on 18/Mar/15
g(1)=f(1)+g(1)⇒f(1)=0  f(xy)=f(x)g(y)⇒f(y)=f(1)g(y)=0  f(x)=0  g(xy)=g(y)  g(x)=g(1) ⇒g(x)=Constant  f(x)g(x)=0
g(1)=f(1)+g(1)f(1)=0f(xy)=f(x)g(y)f(y)=f(1)g(y)=0f(x)=0g(xy)=g(y)g(x)=g(1)g(x)=Constantf(x)g(x)=0

Leave a Reply

Your email address will not be published. Required fields are marked *